Global gridded NOx emissions using TROPOMI observations - A. Rey-Pommier; A. Rey-Pommier; A. Rey-Pommier; A. Héraud; F. Chevallier; P. Ciais; P. Ciais; T. Christoudias; J. Kushta; J. Sciare (Earth System Science Data, 2025)
We present top-down global gridded emissions of NOx for the year 2022. This dataset is constructed from retrievals of tropospheric vertical column densities (VCDs) of NO2 by the TROPOspheric Monitoring Instrument (TROPOMI) spaceborne instrument associated with winds and atmospheric composition data from ECMWF reanalyses, using an improved version of a mass-balance atmospheric inversion. The dataset has a spatial resolution of 0.0625° × 0.0625°, and delivers a detailed overview of the distribution of emissions. It allows the identification of intense area sources, such as cities, and isolated emitters, such as power plants or cement kilns, but does not correctly represent biomass burning. At global level, the emissions obtained are consistent with the EDGARv6.1 bottom-up inventory, although there are differences at regional level, particularly in emerging countries and countries with low observation densities. The emissions of the three largest emitting countries, China, the United States and India, are 6 %, 14 %, and 4% lower than EDGAR estimates, respectively. Uncertainties remain high, and a quantitative analysis of emissions over several averaging periods indicates that averaging emissions uniformly across the year may be sufficient to obtain estimates consistent with annual averages, in regions of the world with high retrieval densities. This dataset is designed to be updated with a low latency to help policymakers monitor emissions and implement energy savings and clean air quality policies. The data can be accessed at https://doi.org/10.5281/zenodo.13758447 as monthly files (Rey-Pommier et al., 2025).